Gut Structure and Microbial Communities in Sirex noctilio (Hymenoptera: Siricidae) and Their Predicted Contribution to Larval Nutrition - Li, Jiale; Li, Chengcheng; Wang, Ming; Wang, Lixiang; Liu, Xiaobo; Gao, Chenglong; Ren, Lili; Luo, Youqing (Frontiers in Microbiology, 2021)
The European woodwasp, Sirex noctilio Fabricius, is a major invasive quarantine pest that attacks and kills pine trees outside of its native range. Insect gut structure and gut microbiota play crucial roles in various life activities. Despite a few reports in nutrition and survival, an extensive study on the S. noctilio larval gut microbiome is lacking. We studied the gut structure using a stereo microscope and used high throughput sequencing of the bacterial 16S rRNA genes and fungal internal transcribed spacer 2 (ITS2) regions to investigate gut microbiota in different developmental stages of S. noctilio, including larvae, adults, and larval frass. We used PICRUSt2 to predict the functional profiles. The larval gut was thin and thread-like from the oral cavity to the anus, carrying few xylem particles in the crop. Pseudomonas, Ralstonia, and Burkholderia s.l were the dominant bacteria in the guts of larvae, adults, and frass, respectively. Even though Pseudomonas was the most abundant among all bacteria, Zoogloea, Ruminobacter, and Nitrosospira, which might be involved in degrading organic matter and fixing nitrogen occurred exclusively in the larval gut indicating their possible role in the growth and development of larvae in pine tree xylem. Fungal communities did not change significantly across different developmental stages or the frass. Amylostereum was dominant in the woodwasp's larval gut. Functional prediction of bacterial and fungal communities revealed that they may encod enzymes involved in degrading lignocellulose and fixing nitrogen. Ours is the first study that compares gut microbial communities present in S. noctilio larvae, adults, and frass. This study could provide an understanding of larval nutrient acquisition in nutrient-deficient host xylem to some extent. Our study may unlock novel strategies for the development of pest management approaches based on interfering with the gut microbiota and restricting their role in larval survival and development.